2019
DOI: 10.3390/molecules24132451
|View full text |Cite
|
Sign up to set email alerts
|

A Citrus Peel Waste Biorefinery for Ethanol and Methane Production

Abstract: This paper deals with the development of a citrus peel waste (CPW) biorefinery that employs low environmental impact technologies for production of ethanol and methane. Three major yeasts were compared for ethanol production in batch fermentations using CPW pretreated through acid hydrolysis and a combination of acid and enzyme hydrolysis. The most efficient conditions for production of CPW-based hydrolyzates included processing at 116 °C for 10 min. Pichia kudriavzevii KVMP10 achieved the highest ethanol prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Temperature also can affect the enzymatic activity and turgidity of yeast cells membrane greatly. It was reported that the performance of S. cerevisiae in bioethanol production is reduced at temperatures higher than 37 o C [31]. This result is in accordance with the study of Vohra et al [32] in which the fermentation temperature for food waste for bioethanol production is in the range of 30-37 o C. This is because the microorganism will becomes more active when warm and dies at high temperature.…”
Section: Effect Of Temperaturesupporting
confidence: 89%
“…Temperature also can affect the enzymatic activity and turgidity of yeast cells membrane greatly. It was reported that the performance of S. cerevisiae in bioethanol production is reduced at temperatures higher than 37 o C [31]. This result is in accordance with the study of Vohra et al [32] in which the fermentation temperature for food waste for bioethanol production is in the range of 30-37 o C. This is because the microorganism will becomes more active when warm and dies at high temperature.…”
Section: Effect Of Temperaturesupporting
confidence: 89%
“…In this mode of operation, any potential toxicant does not reach steady-state levels in the mixed liquor over time. While continuous experiments are one option to study chronic toxicity, repeated re-feeding of the assay once the stable plateau phase of the methane production is reached is another one (Patsalou et al, 2019). Also, due to the short test duration, BMP tests cannot assess the capability of the anaerobic microbial community to adapt to the inhibitor over time (Astals et al, 2015).…”
Section: Inappropriate Applications Of Bmp Testsmentioning
confidence: 99%
“…S7: Fe 2p orbital XPS data of Fe@C-1.0 and spent Fe@C-1.0. [11,26,50,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69].…”
Section: Supplementary Materialsmentioning
confidence: 99%